Calculus - Bradley, Gerald L.; Smith, Karl J. ([S.l.] : Prentice Hall College Div, 1995)
Presents calculus development by integrating technology (with either graphing calculator or computer). The "Computational Windows" feature offers insights into how technological advances can be used to help understand calculus. Also available: Student Survival Manual (0-13-3-5814-X); and Instructor's Solutions Manual (0-13-178732-2).